Effectiveness of selected nursing intervention on level of pain during heel stick prick among the babies admitted in NICU of Dibba hospital, UAE - Dr Sneha Pitre, Resmi S Nair (International Journal of Advanced Science and Technology, 2020)
Background: Pain is a universal phenomena which is experienced by everyone from birth till death. If not managed appropriately in initial stage of life it can have detrimental effect on overall development of the baby. This is especially noteworthy for the babies admitted in NICU as they are often exposed to various painful stimuli, most common is heel stick prick. Methods: Purpose of the study was to evaluate effect of administration of breast milk during heel stick on level of pain among neonates. Total sixty neonates were randomly assigned equally in experimental and control group. Experimental group received extracted breast milk through pacifier during heel stick prick. Level of pain was assessed by using NIPS during heel stick among neonates belonging to experimental and control group. Results: Percentage of female babies was more (51.7%) than male (48.3%). Majority of babies were full term ( 48.35%) as compare to preterm (11.7%) and had normal birth weight (80%).With respect to level of pain administration of breast milk through pacifier to the neonate during heel stick prick has shown positive effect on level of pain as evidence by in control group 63.3% had moderate pain and 13.4 % experienced severe pain as compare to neonates from experimental group majority had mild pain ( 86.7%), 13.3% experienced moderate pain and nobody experienced severe pain. This difference in level of pain was significant at p< 0.05. No association was observed with selected demographic variables such as gender, age and birth weight. Conclusion: Administration of breast milk is a useful non pharmacological method for minimizing pain associated with heel stick prick.